2020
DOI: 10.1542/peds.2019-1623
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Dexmedetomidine for Procedural Distress in Children: A Systematic Review

Abstract: CONTEXT: Intranasal dexmedetomidine (IND) is an emerging agent for procedural distress in children.OBJECTIVE: To explore the effectiveness of IND for procedural distress in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 65 publications
0
51
0
Order By: Relevance
“…Third, although the results of the present study together with previous study (42) indicated the efficacy and safety of intranasal dexmedetomidine administration during breast lumpectomy, future studies need to be conducted to focus on the safety in a larger sample size. Fourth, individual differences in drug tolerance may also provide bias since the time point for surgery was 45 min after intranasal dexmedetomidine was selected according to previous studies (14,(28)(29) instead of plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Third, although the results of the present study together with previous study (42) indicated the efficacy and safety of intranasal dexmedetomidine administration during breast lumpectomy, future studies need to be conducted to focus on the safety in a larger sample size. Fourth, individual differences in drug tolerance may also provide bias since the time point for surgery was 45 min after intranasal dexmedetomidine was selected according to previous studies (14,(28)(29) instead of plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthesia may be an alternative to general anesthesia for this type of surgery ( 5 ). Dexmedetomidine is an effective drug for conscious sedation in patients who undergo minor surgery ( 14 , 17 , 30 , 31 ). A previous study demonstrated that intranasal dexmedetomidine was noninvasive and more tolerable compared with intravenous administration ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations